Pengaruh Penerapan Model Pembelajaran Problem Solving Terhadap Peningkatan Hasil Belajar TIK pada Siswa SMP Negeri 1 Ulujami - Wijayanti, Septiani; Primadiyono, Yohanes; Purbawanto, Sugeng (Jurusan Teknik Elektro Universitas Negeri Semarang, 2017)
The purpose of this study was to determine the effect of the application of problem solving learning model to increase learning outcomes of ICT in class VIII SMP Negeri 1 Ulujami. The method used is a method of quantitative experiments. The population in this study were all students of class VIII SMP Negeri 1 Ulujami the academic year 2015/2016 with the number of 364 students. The research sample is chosen randomly selected classes are two classes as class ekserimen (VIII-A and VIII-G) and two classes as the control class (VIII-C and VIII-I). The results showed the average posttest experimental class learning model of problem solving that is class VIII-A is 86 and VIII-G is 86, while those using the lecture method on the control class is class VIII-C is 79 and VIII-I was 83. the results of the study concluded that there are significant learning model application problem solving to learning outcome of ICT on students of SMP Negeri 1 Ulujami. It can be seen from the results of the linear regression equation VIII-A is Ã½ = 0.29 + 63,79X and the results of the linear regression equation VIII-G is Ã½ = 0.57 + 40,91X means that the effect of variable to variable pretest posttest is positive, showing a rise of the value pretest will be followed by a rise in the value of the posttest.